ANTI-ARTHRITIC ACTIVITY OF AMARANTHUS ROXBURGHIANUS NEVSKI HYDROALCOHOLIC AREAL PLANT EXTRACT IN ACUTE AND CHRONIC MODELS IN ALBINO WISTAR RATS - K, SARAVANAKUMAR; CHIKATIPALLI, RADHIKA; KOTHAPALLI BONNOTH, CHANDRA SEKHAR (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Evaluation of anti-arthritic activity of hydroalcoholic extract of Amaranthus roxburghianus Nevski aerial parts in albino Wistar rats. Materials and Methods: A. roxburghianus dried aerial parts were extracted with ethyl alcohol: water (70:30) ratio, respectively, by the hot Soxhlet method. Hydroalcoholic A. roxburghianus extract (HARE) was further concentrated to obtain a semisolid residue. Two doses 200 and 400 mg/kg of HARE were tested against formaldehyde-induced acute non-immunological and Freund’s complete adjuvant (FCA)-induced chronic immunological arthritis in albino Wistar rats. Arthritis assessment was done by morphological studies (paw volume, paw diameter, and body wt.) and hematological parameters radiological, histopathological, and organ wt. studies were also done on the 28th day after animals were sacrificed. Results: Dose-dependent and significant inhibition of edema were observed in both acute as well as chronic models. The extract at dose 400 mg/kg showed most potent and significant (p<0.05) paw edema inhibition which is supported by the results of paw volume and diameter, hematological parameters, in FCA-induced arthritis model. Treatment with HARE also decreased the histopathological alterations induced by FCA model. Conclusion: HARE protects synovial membrane by improving the health status exhibits promising anti-arthritic activity. This finding thus supports the traditional use of A. roxburghianus for arthritis. However, further studies are needed to carry out the isolation of active constituents of the fraction responsible for the activity.